Disparities in Surgical Care Among Women With Endometrial Cancer. Issue 3 (September 2016) - Mannschreck, Diana; Matsuno, Rayna K.; Moriarty, James P.; Borah, Bijan J.; Dowdy, Sean C.; Tanner, Edward J.; Makary, Martin A.; Stone, Rebecca L.; Levinson, Kimberly L.; Temkin, Sarah M.; Fader, Amanda N.
Abstract : OBJECTIVE: To analyze contemporary U.S. use of minimally invasive surgery for the treatment of endometrial cancer and associated inpatient complications and costs. METHODS: In this retrospective cohort study, the National Inpatient Sample database was analyzed in patients with nonmetastatic endometrial cancer who underwent hysterectomy during 2012–2013. Hierarchical multiple logistic regression and propensity score matching were used to compare complications among patients treated with open compared with minimally invasive hysterectomy surgery. Cost of care was also compared using generalized linear modeling. RESULTS: We identified 9, 799 patients; 52.4% underwent open and 47.6% minimally invasive hysterectomy. Many patients (43.4%) were treated at low-volume hospitals (less than 10 endometrial cancer cases annually). Patients were less likely to undergo open surgery in high-volume compared with low-volume hospitals (51.8% compared with 58.1%, respectively; adjusted odds ratio [OR] 0.35, 95% confidence interval [CI] 0.13–0.94) and more likely to undergo open surgery in rural compared with urban teaching hospitals (75.6% compared with 51.1%, respectively; adjusted OR 14.34, 95% CI 9.66–21.27), government compared with nonprofit hospitals (61.3% compared with 51.1%, respectively; adjusted OR 1.66, 95% CI 1.15–2.39), and in patients of black (67.9%; OR 1.46, 95% CI 1.30–1.65) and "other" race (60.5%; adjusted OR 2.39, 95% CI 1.99–2.87) compared with white race (49.2%, referent). Open surgery was associated with increased perioperative complications (adjusted OR 2.80, 95% CI 2.48–3.17) and a 1, 243 increase in cost per case compared with minimally invasive approaches ( P <.001). Using minimally invasive surgery for 80% of study patients may have averted 2, 733 complications and saved approximately 19 million. CONCLUSION: Most U.S. women with endometrial cancer continue to be treated with open hysterectomy surgery despite increased complication rates and financial costs associated with this approach. A disparity in endometrial cancer surgical care exists that is affected by patient race and hospital geography and cancer volumes. Abstract : Most U.S. women with endometrial cancer continue to be treated with open hysterectomy surgery despite increased complication rates and financial costs associated with open surgery.